2000
DOI: 10.1106/uy9u-f2qw-2fkk-91kg
|View full text |Cite
|
Sign up to set email alerts
|

A New Method to Reduce Cure-Induced Stresses in Thermoset Polymer Composites, Part III: Correlating Stress History to Viscosity, Degree of Cure, and Cure Shrinkage

Abstract: Non-thermoelastic effects such as cure shrinkage of a polymer can play a role in residual stresses in composite parts. Studies have shown that cure shrinkage can place significant stresses on fibers. Therefore, the cure cycle of 3501-6 epoxy resins was modified to change its cure shrinkage characteristics to minimize the stresses. New cure strategies were developed using volumetric dilatometry, differential scanning calorimetry, dielectric cure monitoring, and a unique single fiber stress test method. Cure cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 6 publications
0
35
0
Order By: Relevance
“…This design requires the venting of air from the plastic pouch and the confining oil. Russell et al [8] used a PVT (Pressure Volume Temperature) apparatus for the measurement of volumetric shrinkage of epoxy resins. The two designs mentioned seem to have the ability to measure the shrinkage of thermoset resins during cure.…”
Section: Introduction Tmentioning
confidence: 99%
“…This design requires the venting of air from the plastic pouch and the confining oil. Russell et al [8] used a PVT (Pressure Volume Temperature) apparatus for the measurement of volumetric shrinkage of epoxy resins. The two designs mentioned seem to have the ability to measure the shrinkage of thermoset resins during cure.…”
Section: Introduction Tmentioning
confidence: 99%
“…[27], Russel et Al. [28] and Mergheim et Al. [29] also concluded that chemical shrinkage should be considered in the evaluation of residual stresses.…”
Section: Introductionmentioning
confidence: 88%
“…After demolding, the composite is usually post-cured at an elevated temperature above T g . During this process, the stresses induced by curing can be significantly relaxed [24][25][26]. For some resin systems, such as epoxy, the curing strain during conversion can be neglected in the analysis of residual stress [27].…”
Section: Spring-in Modelmentioning
confidence: 99%